Analisis tren pola curah hujan di Wilayah Manado dan sekitarnya - Brilliant Abraham Wallah; Tiny Mananoma; Cindy Jeane Supit (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2025)
Flood disasters are one of the major issues frequently occurring in Manado City, Indonesia, particularly during the rainy season. These floods are influenced by various factors, including changes in land use, deforestation in upstream river areas, river sedimentation, inadequate drainage systems, and extreme rainfall. Climate change also significantly impacts the hydrological cycle, including the intensity, frequency, and distribution of rainfall. Manado City is highly vulnerable to increased rainfall intensity, especially during specific months. Therefore, analyzing rainfall pattern changes over the past 50 years is crucial for a deeper understanding of their impacts. This study aims to identify trends in rainfall pattern changes in the Manado region and its surroundings over the last 50 years. The analysis focuses on several variables, including annual average rainfall, maximum daily rainfall, the number of rainy days per year, months with maximum daily rainfall, and average monthly rainfall. Rainfall data were obtained from three observation stations: Sam Ratulangi Meteorological Station, North Sulawesi Climatology Station, and Bitung Maritime Meteorological Station. Statistical analysis was conducted using linear regression and the Mann-Kendall Trend method to determine data trends. The analysis results indicate that the annual average rainfall trend has increased at all observation stations. Maximum daily rainfall shows a significant increasing trend at North Sulawesi Climatology Station, while the increases at the other two stations are not significant. The number of rainy days per year also shows an increasing trend at all stations, though not significantly. The distribution of maximum daily rainfall frequency tends to occur at the beginning of the year (January) and the end of the year (December), with decreasing frequency in the following months until mid-year. This distribution pattern forms a "U" or "V" shape at Sam Ratulangi Meteorological Station and North Sulawesi Climatology Station, whereas at Bitung Maritime Meteorological Station, rainfall patterns are more evenly distributed throughout the year. Additionally, average monthly rainfall shows an increasing linear trend in almost all months at all observation stations. This study contributes to the understanding of rainfall pattern changes, which can serve as a basis for spatial planning, disaster mitigation, and the adaptive design of infrastructure to cope with climate change in urban areas such as Manado.